Analysis of the Specificity and Biochemical Characterization of Metalloproteases Isolated from Eupenicillium javanicum Using Fluorescence Resonance Energy Transfer Peptides - Hamin Neto, Youssef A. A.; de Oliveira, Lilian C. G.; de Oliveira, Juliana R.; Juliano, Maria A.; Juliano, Luiz; Arantes, Eliane C.; Cabral, Hamilton (Frontiers in Microbiology, 2017)
Enzymes have important features that may facilitate their application in industrial processes and have been used as alternatives to chemical catalysts. In particular, proteases can be isolated from microorganisms, which provide important sources of advantageous enzymes for industrial processes. For example, Eupenicillium javanicum is a filamentous fungus that has been shown to express industrially applicable enzymes and chemical components, such as antifungal compounds. The biotechnological potential of Eupenicillium javanicum and proteases made us search a novel protease from this microorganism. The macromolecule was isolated, the main biochemical properties was evaluated, and the specificity of the protease subsites was determined. The protease was produced under solid-state bioprocess with wheat bran and isolated by two chromatography steps with yield of 27.5% and 12.4-fold purification. The molecular mass was estimated at 30 kDa. The N-terminal sequence of the first 20 amino acid residues was AVGAGYNASVALALEKALNN. The enzyme presented higher proteolytic activity at pH 6.0 and 60 °C. The protease is stable at wide range of pH values and temperatures and in the presence of surfactants. The “primed” side of the catalytic site showed the highest catalytic efficiency of the enzyme isolated from E. javanicum. The S’1 subsite is responsible for catalyzing the protease reaction with substrates with tyrosine in P’1. These findings provide important insights into the biochemical characterization of a highly active protease from E. javanicum and may facilitate the development of industrial processes involving this protease.